2005
DOI: 10.1136/bjo.2004.052787
|View full text |Cite
|
Sign up to set email alerts
|

Importance of early morning intraocular pressure recording for measurement of diurnal variation of intraocular pressure

Abstract: LETTERS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Numerous studies in the last decades have shown that IOP in humans undergoes circadian variations, with higher peaks in the morning and lower ones in the afternoon and evening. [1][2][3] It is also well known that IOP varies with the body position. IOPs have been reported to be higher when the patient's body is in the supine position (SUP) than in the upright position (UP).…”
mentioning
confidence: 99%
“…Numerous studies in the last decades have shown that IOP in humans undergoes circadian variations, with higher peaks in the morning and lower ones in the afternoon and evening. [1][2][3] It is also well known that IOP varies with the body position. IOPs have been reported to be higher when the patient's body is in the supine position (SUP) than in the upright position (UP).…”
mentioning
confidence: 99%
“…2 Diurnal variations can affect the reliability of IOP measurements, and thus also influence diagnosis and follow-up of ocular hypertension and the corresponding therapeutic strategy, which is very important to clinical practice and research activity. [3][4][5] However, other cornea-related properties could be implicated as one source of IOP measurement variation, including the biomechanical properties of the cornea.…”
mentioning
confidence: 99%
“…11,12 The relationship of IOP with the systemic parameters need a special concern as raised IOP is the only modifiable risk factor for glaucoma. 13 The development of optic nerve damage and visual field defects are more likely associated with the raised IOP. 14 Most of the available data about prevalence of glaucoma in India is from the south and the north India.…”
Section: Discussionmentioning
confidence: 99%